Development Of Glycol Skid Unit Controller Using PLC - Abdul Manaf, Mohd Nadirul Azwan (Universiti Teknologi PETRONAS, 2011)
The purpose of this project was to introduce an activity of using the ladder diagrams on the learning of programmable logic controller (PLC). Unlike generalpurpose computers, the PLC is designed for multiple inputs and output arrangements, and resistance to vibration and electrical noise. Programs to control machine operation are typically stored in non-volatile memory. PLC is a user friendly, microcontroller based, specialized computational device that can carry out many of control function such as distributed control system, process and motion. The advantages of PLC make it a brain of modem industrial control system and this reason, learning PLC operation is very important for modem industrial technologies. PLC can be employed to control processes or machine operations and they offer industrial control systems a very high flexibility of their application. Nowadays, they are becoming very popular among the field of industrial controls of various types. With varying in size and functions, this electronic device are becoming the standard controllers and rapidly replacing the available electronic and pneumatic controllers that still using the hardwire system